Karakteristik Oseanografi dan Musim Penangkapan Ikan Kembung (Rastrellinger sp.) di Laut Natuna: Karakteristik Oseanografi dan Musim Penangkapan Ikan Kembung (Rastrellinger sp.) di Laut Natuna - Apriansyah, Apriansyah; Utami, Pratita Budi (Jurnal Kelautan, Lingkungan, dan Perikanan, 2024)
The improvement of Indian mackerel fishing activities in the Natuna Sea can be accomplished by providing information about water characteristics to analyze the optimal fishing timing. This study aimed to investigate the water characteristics that affect Indian mackerel fisheries using data from CROCO model (sea surface temperature and salinity) and Indian mackerel (Rastrellinger sp.) landing data at the Pemangkat Nusantara Fishing Port. The results showed that the peak of the Indian mackerel fishing season occurred from southwest to northeast. During this period, the waters of the Natuna Sea were characterized by warm temperatures (greater than 29 °C) and low salinity (less than 33 PSU). During this period, the relatively stable and less extreme water conditions in the Natuna Sea were associated with the high abundance of mackerel in these waters.